Prospects and Challenges of Multi-Stakeholder Cooperatives in Supporting Community-Based Economy in Indonesia - Asep Koswara; Ervan Taofik; Erik Andriana; Jati Gunawan; Leni Maria (Review of International Economic, Taxation, and Regulations, 2025)
Multi-stakeholder cooperatives (KMPs) play a crucial role in fostering economic inclusivity and sustainability within Indonesia’s community-based economy. This study examines the effectiveness of KMPs, identifies key challenges in governance, financing, and stakeholder coordination, and explores strategic solutions to enhance their impact. Findings reveal that KMPs promote equitable economic participation, support local entrepreneurship, and encourage long-term financial stability. However, challenges such as governance complexities, limited access to capital, and stakeholder misalignment hinder their effectiveness. Regional variations further influence the success of KMPs, highlighting the need for tailored policy interventions. Despite these challenges, emerging opportunities—such as digitalization, alternative financing models, and strengthened regulatory support—offer potential pathways for growth. To maximize the impact of KMPs, targeted policies, improved financial mechanisms, and stronger multi-sector collaborations are essential. By addressing these issues, KMPs can serve as transformative economic models, fostering sustainable development and enhancing resilience in local economies across Indonesia.